Assessment of the shaping ability of three systems used in long oval canals (Research, Society and Development, 2021)
The aim of this study was to analyze volume variation, untouched walls, transportation, and centralization in long oval canals prepared with ProTaper Next (PTN), X File (XF) and X Gray (XG) by microcomputed tomography (micro-CT). Forty-five lower incisors were divided into three groups (PTN, XF and XG) with 15 specimens each, according to the micro-CT pre-instrumentation (PI) analysis. After the use of each instrument new exams were performed. Volume variation and untouched walls data were analyzed by two-way ANOVA, and for the first one, Tukey HSD or Games-Howell tests were applied in the sequence; data of transportation and centralization were compared by Kruskal-Wallis and Mann-Whitney test. The statistical significance was set at p < 0.05. Between thirds, higher wear values were found in the cervical (p